Answer:
(x,y)→(y,-x)
Step-by-step explanation:
Parallelogram ABCD:
A(2,5)
B(5,4)
C(5,2)
D(2,3)
Parallelogram A'B'C'D':
A'(5,-4)
B'(4,-5)
C'(2,-5)
D'(3,-2)
Rule:
A(2,5)→A'(5,-2)
B(5,4)→B'(4,-5)
C(5,2)→C'(2,-5)
D(2,3)→D'(3,-2)
so the rule is
(x,y)→(y,-x)
Answer:
70
Step-by-step explanation:
it depends on the grade you make, so if you were to make a 65.47, your grade would be a 70, so any grade less than 70 should be the answer, hope this helps!
Answer:
75%
Step-by-step explanation:
Answer:
k = 5
Step-by-step explanation:
I will assume that your polynomial is
x^2 - 3x^2 + kx + 14
If x - a is a factor of this polynomial, then a is a root.
Use synthetic division to divide (x - 2) into x^2 - 3x^2 + kx + 14:
2 / 1 -3 k 14
2 -2 2k - 4
-------------------------------------
1 -1 (k - 2) 2k - 10
If 2 is a root (if x - 2 is a factor), then the remainder must be zero.
Setting 2k - 10 = to zero, we get k = 5.
The value of k is 5 and the polynomial is x^2 - 3x^2 + 5x + 14
You can just do the inverse operation. 39 divied by 10 = 3.9
so 3.9 *10 =39
hope it helped